PERSEPSI SIVITAS AKADEMIKA DI UPBJJ-UT TERHADAP PEROLEHAN SERTIFIKAT ISO 9001:2008 - Diarsi Eka Yani; Argadatta Sigit; Tuty Maria Wardiny (LPPM Universitas Terbuka, 2011)
The management quality standard of UT student services is based on ISO 9001. Recently ISO 9001:2008 certificate already being applied to 35 UT Regional Centres (UPBJJ-UT). UT has to allocate considerable amout of budget in order to maintain them. Considering the limitattion of budget in the future, a study had to be conducted in order to collect information on the perception of Academicians community toward the benefit on implementing ISO 9001:2008. The purposes of the study were (1) to identify the benefits of ISO certification, (2) to identify the perceptions of colleagues and students toward the acquisition of ISO certification, and (3) to explain the relations between UPBJJ-UTs characteristics based on their geographical conditions, their partners and students perceptions toward the acquisition of ISO certificate. The research methodology applied the standard survey, by submitting questionnaire to the UPBJJ-UTs leaders, staffs, partners and students at 10 UPBJJ-UT which were characterized by urban, islands, and inland. Data was analysed by applying descriptive statistics methods. The result showed that : (1) the officials in the UPBJJ management level felt that ISO as procedures were very useful for managing the office administration, however some procedures need to be modified and readapted to make them better, more realistic and humanist (2) the achievement of ISO certificate did not have any influence to UT colleagues and studentss peceptions towards UT (3) Based on UPBJJ-UT characteristics, it seemed thatthere were no differences in perceptions among UT partners and students toward UTs ISO certificate.